Tocopherols and tocotrienol content of hazelnut cultivars grown in Portugal - Amaral, Joana S. (2010)
The effect of roasting on some nutritional characteristics of hazelnut lipidic fraction was investigated. Hazelnuts (Corylus avellana L.) were submitted to several different thermal treatments, comprising different temperatures (125-200 °C) and times of exposure (5, 15, and 30 min) and analyzed for their moisture and crude fat. Raw and roasted hazelnuts were also analyzed for their compositions in phytosterols and fatty acids (including trans isomers) by GC-FID, triacylglycerols by HPLC-ELSD, and tocopherols and tocotrienols by HPLC-DAD/fluorescence spectroscopy. Minor changes occurred in the fatty acid and triacylglycerol compositions. As temperatures and roasting periods increased, generally, a modest increase of oleic and saturated fatty acids and a decrease of linoleic acid, expressed as relative percentages, occurred. Similarly, an increase of triacylglycerols containing oleic acid moieties and a decrease of those containing linoleic acid moieties were found in the roasted samples. Roasting caused a modest decrease of the beneficial phytosterols (maximum 14.4%) and vitamin E homologues (maximum 10.0%) and a negligible increase of the trans fatty acids.